위성항법시스템의 전리층 보정 가능 영역 확장을 위한 인공 신경망의 성능 분석 - 류경돈; Gyeong-don Ryu; 소형민; Hyoungmin So; 박흥원; Heung-won Park (한국항행학회논문지, 2018)
광역 차분위성항법시스템의 서비스 영역을 기준국 네트워크 외부로 확장하기 위해서는 전리층 보정 정보의 외삽이 필수적이다. 본 논문에서는 전리층 보정 영역 확장을 위한 인공 신경망을 설계하고 이에 대한 성능분석을 수행하였다. 인공 신경망 입력으로 사용되는 일/년별 주기함수, 태양흑점개수, 자기장 인덱스(Ap)의 개별 요소들이 전리층 외삽 추정 성능에 미치는 영향을 분석하였다. 신경망의 구성에 있어서는 은닉 층의 수 및 뉴런 개수 변화에 따른 성능 분석을 수행하였다. 분석결과를 바탕으로 신경망을 구현하고 태양활동 극대기(2014년)의 고위도와 저위도 지역에서의 전리층 추정 결과를 보였다. Extrapolating the correction information of ionosphere is essential for expanding wide area differential GPS (WADGPS) service area beyond the reference station network. In this paper, design and analysis of the artificial neural network for expanding the ionospheric correction region will be proposed. First, analysis about influence of each input of neural network were performed. The inputs are the day/year periodic function, sunspot number, and geomagnetic index (Ap). Second, performance analysis with respect to the number of hidden layers and neurons in the neural network is shown. As a result, estimation of total electron contents (TEC) on the high/low latitude regions in solar max(2014) are displayed.